Effect of roasted soy-nut supplementation on lipid profile of Iranian postmenopausal women. - Yazdekhasti, Narges; Yassin, Zaitun; Mohd Esa, Norhaizan; Boushehri, Syed Najafpour (IDOSI Publications, 2011)
The present study was carried out to study the effect of roasted soy-nut consumption on the lipid profile of postmenopausal women. Randomized Controlled trial was conducted using 100 postmenopausal women aged 45-60 years. Participants in the treatment group were provided with 75g roasted soy-nut for daily intake for 2-months. The participants in the control group were asked not to change their usual dietary habits and lifestyles and all were instructed to avoid taking soybean and soybean products. The changes in blood lipid profile were measured beside some other outcome measures comprised of anthropometry, dietary variables and lifestyle questionnaires, measured at baseline and at the end of the study. Results revealed significant (p<.005) differences in ApoAI were observed between two groups at baseline. The t-test only showed significant (p<.005) difference in the mean total cholesterol (TC) between the treatment and control groups after two months intervention. Using the General Linear Model (GLM) for repeated measures, significant mean differences were observed for TC (-5.58%), low-density lipoprotein cholesterol (LDL-C) (-9.54%), non-high density lipoprotein cholesterol (HDL-C) (-7.34%), apolipoprotein A (12.26%) and apolipoprotein B (-7.69%). I No significant differences in triglyceride (TG), HDL-C and the ratio of ApoB: ApoAI from GLM were reconfirmed using Analysis of Covariance. In conclusion: A short-term intake of roasted soy-nut improved the lipid profile of the postmenopausal subjects.